Sustainability Key Performance Indicators for Thailand’s Upstream Oil and Gas Industry - Atsavakovith, Chatrudee; Suthiwartnarueput, Kamonchanok; Pornchaiwiseskul, Pongsa (Arts of Management Journal, 2022)
This article aimed to study and propose key performance indicators and sustainability models for Thailand’s upstream oil and gas industry. This propose is based on a literature review and a survey of academicians and industry experts to achieve sustainable operations. The analytical hierarchy process adopted prioritizes indicators based on triple bottom line aspects. The oil and gas exploration and production industry is one of the most important for driving a nation’s economy. Additional income is generated through royalty payments, special remuneration benefits, petroleum income tax, and revenues from joint development. However, the business carries high risk, including the uncertainty of unproven geological reserves; high cost of production; high intervention and maintenance costs; dependency of production capability on the weather; price fluctuations; and cost of treatment of waste and spills. Therefore, the industry makes efforts to be more sustainable by causing less harm to the environment and society while making profits, building relationships with partners and investors, and enhancing its competitive advantage for long-term benefits to the bottom line. Even in times of low energy demand, the momentum and intensity to measure sustainability in the upstream oil and gas industry are maintained. As we move towards a more sustainable future, the upstream oil and gas sector should be considered a sustainable indicator to verify overall performance and measurable. Moreover, the oil and gas industries in Thailand’s upstream sector are increasingly challenged to maintain business integrity. To ensure national energy security, the proposed sustainability KPIs and sustainability model could be used as guidance.